Metabolic acidosis and anaemia associated with dorzolamide in a patient with impaired renal function - Hoffmanová, Iva; Sánchez, Daniel (British journal of clinical pharmacology, 2018)
Topical carbonic anhydrase inhibitors (CAI), used for treatment of glaucoma, are generally regarded as safe and unconnected with systemic side effects. We report an unusual case of fatigue, metabolic acidosis, and normocytic anaemia associated with ocular administration of the CAI, dorzolamide, in a patient with impaired renal function. In chronic kidney disease, where CAI elimination may be decreased, and patients prone to develop metabolic acidosis, systemic absorption of ocular administered CAI could lead to rare, but potentially serious adverse reaction, that are a consequence of inhibition of extraocular carbonic anhydrase isoenzymes.
Keywords: renální insuficience; Carbonic Anhydrase Inhibitors; Anemia; Glaucoma; únava; thiofeny; Acidosis; lidé; Fatigue; Sulfonamides; acidóza; inhibitory karboanhydras; Thiophenes; Male; glaukom; sulfonamidy; lidé středního věku; anemie; mužské pohlaví; Renal Insufficiency; aplikace oční; Middle Aged; Administration, Ophthalmic; Humans